Associations Between Obesity Indicators and Blood Pressure in Chinese Adult Twins. (20th January 2017) - Liao, Chunxiao; Gao, Wenjing; Cao, Weihua; Lv, Jun; Yu, Canqing; Wang, Shengfeng; Zhao, Qian; Pang, Zengchang; Cong, Liming; Wang, Hua; Wu, Xianping; Li, Liming
Abstract : Obesity is associated with blood pressure (BP), but the associations between different obesity indicators and BP have not reached agreement. Besides, both obesity and BP are influenced by genetic and environmental factors. Whether they share the same genetic or environmental etiology has not been fully understood. We therefore analyzed the relationship between different obesity indicators and BP components as well as the genetic and environmental contributions to these relationships in a Chinese adult twin sample. Twins aged 18–79 years ( n = 941) were included in this study. Body mass index (BMI) was used as the index of general obesity, whereas waist circumference (WC), waist-to-height ratio (WHtR), and waist-to-hip ratio (WHR) were used as the indicators of central obesity. BP components included systolic blood pressure (SBP) and diastolic blood pressure (DBP). Linear regression models and bivariate structural equation models were used to examine the relation of various obesity indicators with BP components, and genetic or environmental influences on these associations, respectively. A strong association of BP components with BMI—and a somewhat weaker association with WC, WHtR, and WHR—was found in both sexes, independent of familial factors. Of these phenotypic correlations between obesity indicators and BP components, 60–76% were attributed to genetic factors, whereas 24–40% were attributed to unique environmental factors. General obesity was most strongly associated with high BP in Chinese adult twins. There were common genetic backgrounds for obesity and BP, and unique environmental factors also played a role.